Impak Peraturan Formal, Tidak Formal dan Amalan Mesra Alam Terhadap Pematuhan Industri Pembuatan di Utara Semenanjung Malaysia - Mohd Nasir, Nawawi (2012)
Malaysia without exception confronts with the environment pollution resulting from a rapid manufacturing sector development. While manufacturing sector is the main engine of the economic growth for this country, it is the second largest contributor to river pollution. In managing pollution issues many countries adopt various protective approaches from command-and-control system to those of the market-based incentive. In Malaysia, the Environmental Quality Act 1974 has been perceived as adequate and comprehensive to control the behavior of industries. Nevertheless, the effectiveness of this regulation depends on the firm’s decision to comply with the rules subject to cost and benefit considerations. Therefore, understanding the compliance behavior of the industry would help the policy makers to design more effective regulations. The purpose of this study is to identify factors that influence the compliance of industry to the effluent regulations that comprise of formal regulations, informal regulations and environmental management system ISO 14001. A modification of criminal behavior model by Becker (1968) has been applied to estimate the dichotomous compliance decision using econometric model of logistic regression. The results of the study indicated that the firm’s compliance was influenced by the probability of fined and gains from illegal activities. Since the cost of operations of the effluent treatment system was used as the proxy for illegal gains, the firm would comply with the regulations if the cost did not exceed 6.4 percent per month. Further analysis also estimates that the firm would comply if the expected fine was less than 35 percent. From the side of non-regulation factors, it was discovered that firm complying with regulations received higher pressure from the informal regulation component. However, ISO 14001 certifications had no significant influence on the firm’s compliance. The result of the empirical analysis suggest that effluent treatment policies require efforts to reduce the cost of operations of the effluent treatment system incurred by the firm with respect to financial and technical support. The enforcement agency also requires more systematic inspection strategies and that fine mechanism should be the last resort.